LncRNA-ENST00000543604 exerts a tumor-promoting effect via miRNA 564/AEG-1 or ZNF326/EMT and predicts the prognosis of and chemotherapeutic effect in colorectal cancer - Wang, Weimin; Zhou, Zhen; Dai, Xiaojun; Wang, Haibo; Jin, Jun; Min, Ke; Wang, Yunfan; Lv, Mengying; Liu, Yanqing; Zhou, Yan (Frontiers in Oncology, 2022)
Objectives:: Colorectal cancer is a common malignant tumor. Recent studies have found that lncRNAs play an important role in the occurrence and development of colorectal cancer. Methods: Based on high-throughput sequencing results of fresh CRC tissues and adjacent tissues, we identified lncRNA-ENST00000543604 (lncRNA 604) as the research object by qRT-PCR in CRC tissues and cells. We explored the mechanism of lncRNA 604 action by using luciferin reporter, qRT-PCR and Western blot assays. Kaplan-Meier survival analysis and a Cox regression model were used to analyze the correlation of lncRNA 604 and its regulatory molecules with the prognosis of and chemotherapy efficacy in CRC patients. Results: In this study, we found that the expression levels of lncRNA 604 were increased in CRC. LncRNA 604 could promote CRC cell proliferation and metastasis through the miRNA 564/AEG-1 or ZNF326/EMT signaling axis in vivo and in vitro. LncRNA 604 could predict the prognosis of CRC and was an independent negative factor. LncRNA 604 exerted a synergistic effect with miRNA 564 or ZNF326 on the prognosis of CRC. LncRNA 604 could improve chemoresistance by increasing the expression of AEG-1, NF-κB, and ERCC1. Conclusions: Our study demonstrated that lncRNA 604 could promote the progression of CRC via the lncRNA 604/miRNA 564/AEG-1/EMT or lncRNA 604/ZNF326/EMT signaling axis. LncRNA 604 could improve chemoresistance by increasing drug resistance protein expression.